Juridical Analysis Of The Crime Of Sexual Violence Against Children Based On Law Number 12 Of 2022 Concerning The Crime Of Violence Sexual And Legal Number 35 Of 2014 Concerning Child Protection - Risa Damayanti; Yasmirah Mandasari Saragih (Yayasan Multidimensi Kreatif, 2024)
Sexual violence is a deviation in societal sexual practices, characterized by coercive and violent actions that contradict social norms. One common form is sexual harassment, involving unwelcome sexual advances that disturb victims. Sexual violence affects individuals of all ages, from children to the elderly, degrading human dignity and disrupting societal peace. It is a constitutional right for citizens to be protected from such violence, as guaranteed by the 1945 Constitution. The digital realm has seen a surge in sexual violence cases, with 2021 recording the highest number of gender-based cases. Komnas Perempuan's annual report highlights various forms of online sexual violence, including cyber harassment, malicious distribution, and sextortion. The definition of sexual violence extends beyond physical acts to include psychological abuse and humiliation. Law Number 12 of 2022 categorizes several forms of sexual violence, including non-physical harassment, abuse, forced contraception, and electronic-based violence. Additionally, acts like rape, forced prostitution, and child exploitation are also recognized. Indonesia has ratified international conventions to eliminate torture and discrimination. However, the current Criminal Procedure Law inadequately protects victims, focusing more on defendants' rights. Article 23 of Law Number 12 of 2022 restricts resolving sexual violence cases outside the judicial process, except for child perpetrators. This study is titled